Prediction of physiological status, community participation, and daily activity function to sleep quality for outpatient dynapenic older people - Hsiao-Chi Tsai; Shu-Fang Chang (BMC Geriatrics)
Abstract Background The global aging population has increased dynapenia prevalence, leading to mobility issues and poor sleep quality among older adults. Despite its impact, research on sleep quality in dynapenic outpatients is limited. This study investigates how physiological status, community participation, and daily activity function influence sleep quality in this group. Methods This cross-sectional study employed purposive sampling to collect data from 192 dynapenic older outpatients in October 2022, assessing their basic attributes, physiological status, community participation, daily activity function, and sleep quality. Data were analyzed using SPSS 25.0 for descriptive statistics, independent samples t-tests, chi-square tests, and logistic regression analysis. Results Findings indicated significant correlations between sleep quality and gender (X2 = 11.340, p < .001), occupational status (X2 = 13.378, p < .05), residence (X2 = 6.265, p < .05), medication intake (X2 = 7.250, p < .05), smoking history (X2 = 6.695, p < .01), instrumental activities of daily living (X2 = 12.556, p < .01), activities of daily living (t = 2.74, p < .01), instrumental activities of daily living (t = 3.60, p < .001), skeletal muscle mass (t = 2.94, p < .01), skeletal muscle index (t = 2.65, p < .01), grip strength (t = 3.61, p < .001), and walking speed (t = 2.09, p < .05). Furthermore, the type of occupational status (OR = 6.608, 95% CI = 1.124–3.744, p < .05), medication intake (OR = 3.916, 95% CI = 1.682–9.114, p < .05), and grip strength (OR = 0.891, 95% CI = 0.797–0.996, p < .05) were significant predictors of sleep quality in dynapenic older patients. Conclusion This cross-sectional study reveals significant correlations between sleep quality and key factors such as physiological status, community participation, and daily functional activities in older adults with dynapenia. These findings underscore the importance of addressing these determinants to enhance sleep quality in this population.